2014
DOI: 10.1186/1472-6882-14-5
|View full text |Cite
|
Sign up to set email alerts
|

Cynomorium songaricum extract enhances novel object recognition, cell proliferation and neuroblast differentiation in the mice via improving hippocampal environment

Abstract: BackgroundCynomorium songaricum Rupr. (CS) has been used as a medicine to treat many diseases as well as to alleviate age-related issues, such as memory impairment, dementia, and stress. In this study, we assessed the effects of Cynomorium songaricum extract (CSE) on the novel object recognition, cell proliferation and neuroblast differentiation in the dentate gyrus of mice by using 5-bromodeoxyuridine (BrdU) and polysialylated neural cell adhesion molecule (PSA-NCAM). We also measured serum corticosterone lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Adult neurogenesis can be affected by variables, such as environmental factors, growth factors, neurotransmitters, and external stimuli that alter the affective state of an animal [46]. Herbal supplementation can also modulate neurogenesis and thereby affect hippocampal functions, such as memory [79]. However, few studies have focused on the oil components of foods consumed in high quantities in oriental countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult neurogenesis can be affected by variables, such as environmental factors, growth factors, neurotransmitters, and external stimuli that alter the affective state of an animal [46]. Herbal supplementation can also modulate neurogenesis and thereby affect hippocampal functions, such as memory [79]. However, few studies have focused on the oil components of foods consumed in high quantities in oriental countries.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we demonstrated that S -allyl-L-cysteine, a water-soluble component of Allium species [21, 22], promotes cell proliferation and neuroblast differentiation in the dentate gyrus [7]. In addition, we have shown the neuroprotective effects of Z -ajoene, an oil-soluble component, against ischemic damage in the gerbil hippocampus [9]. On the other hand, the administration of 10 mg/kg DADS affects neurogenesis, by reducing hippocampal brain-derived neurotrophic factor (BDNF) levels, and impairs performance in the passive avoidance test [23].…”
Section: Introductionmentioning
confidence: 99%
“…It is grown up in Gansu Province, China. This plant also possesses significant biological functions [ 6 , 14 , 15 ]. The samples were carefully handled as described with C. coccineum and stored at −20 °C for future use.…”
Section: Methodsmentioning
confidence: 99%
“…Hippocampal CA1 region, CA3 region, and dentate gyrus was dissected under stereoscope and tissue samples were immediately immersed in RNAlater solution (Qiagen) and RNA extraction was performed using a total RNA isolation kit (Macherney-Nagel). RT-qPCR was performed as described in the previous studies [12,26] and the primers used were as follows: 5′-GGACATCGAG ACACCAGGAT− 3′ (forward) and 5′-AGGTGCCTGT TGAGCACTCT-3′ (reverse) for FTO (accession number: NM_011936) and 5′-GCACCACACCTTCTA CAATG-3′ (forward) and 5′-TGCTTGCTGATCCACATCTG-3′ (reverse) for β-actin.…”
Section: Rt-qpcr Experimentsmentioning
confidence: 99%